New Direction of the Qur'an Interpretation in Indonesia: A Study of Nadirsyah Hosen's Interpretation on Social Media - Ashfiya', Rofiqoh Nurul (Al-Karim: International Journal of Quranic and Islamic Studies, 2024)
This article examines the interpretation of Qur'anic verses on social media by Nadirsyah Hosen. The study employs a library research method with an analytical approach, collecting data from Hosen's posts on his Facebook page. The focus is on his interpretation of controversial Qur'anic verses in response to socio-political issues in Indonesia. The findings reveal that Qur'anic interpretation on social media tends to simplify complex exegetical discourse to align with the platform's fast-paced and accessible nature. This phenomenon contributes to the democratization of tafsir, enabling broader public engagement but also raising concerns about the validity and authority of interpretations. Furthermore, the study highlights how Hosen's contextual approach situates the Qur'an within contemporary social realities, making it more relevant to modern challenges. His method reflects a shift in Qur'anic interpretation in Indonesia, where social media facilitates a more inclusive and dynamic exegetical discourse. However, the absence of rigorous academic verification mechanisms in digital tafsir poses the risk of misinterpretation and epistemological inconsistencies. Given these dynamics, future research should explore strategies for integrating academic verification into digital Qur'anic interpretation to ensure methodological robustness. Additionally, this study is limited to the analysis of a single figure, Nadirsyah Hosen. Comparative research examining multiple digital exegetes and their interpretative frameworks would provide a more comprehensive understanding of the evolving landscape of Qur'anic interpretation in the digital era. Contribution: This study highlights the role of social media in democratizing Qur'anic interpretation while underscoring challenges to its authority and academic rigor.